TINDAK PIDANA PENIPUAN DALAM TRANSAKSI ELEKTRONIK BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DAN PENEGAKAN HUKUM NYA TERHADAP PENIPUAN TIKET KONSER WE ALL ARE ONE MELALUI MEDIA TIKET.COM - Ramadhan, Rizki; Pravitri, Ivana Meilani; Siskarina, Melvy Dwi; Ul Hosnah, Asmak (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2023)
Along with the rapid development of technology in the digital era, the faster the exchange of information and culture both from outside countries to our country and vice versa. In this case, we will discuss in more detail about K-POP culture that is being loved among teenagers to adults. Not infrequently with the increasing enthusiasm of Indonesian people who love K-POP, many people are very enthusiastic to be able to meet their idols. And the most common way to meet his idol is by attending a music concert organized by his agency or from another promotor event. To be able to attend the concert in order to meet his idol, the event promoter will sell tickets that can be purchased by the public through various online media platforms. But not infrequently this becomes a loophole and opportunity for criminals to reap profits from online ticket sales fraud. This research is a qualitative research type with data sources from interviews with one of the victims of WE ARE ALL ONE concert ticket sales fraud. This research aims to provide knowledge to the public as a prevention of fraud, especially in the case of fraudulent online ticket sales. Keywords: Fraud, Concert tickets, K-POP.